Polymer-supported ionic liquid solid phase extraction for trace inorganic and organic mercury determination in water samples by flow injection-cold vapor atomic absorption spectrometry - Escudero, Leticia Belén (2013)
A simple and green technique named polymer-supported ionic liquid solid phase extraction (PSIL-SPE) was developed for mercury (Hg) species determination. Inorganic Hg (InHg) species was complexed with chloride ions followed by its introduction into a flow injection on-line system to quantitatively retain the anionic chlorocomplex (HgCl42−) in a column packed with CYPHOS® IL 101-impregnated resin. The trapped InHg was then reduced with stannous chloride (SnCl2) and eluted with the same flow of reducing agent followed by cold vapor atomic absorption spectrometry (CV-AAS) detection. Organic mercury species (OrgHg) did not interact with the impregnated resin and were not retained into the column. Total concentration of OrgHg was evaluated by difference between total Hg and InHg concentration. A 95% extraction efficiency was achieved for InHg when the procedure was developed under optimal experimental conditions. The limit of detection obtained for preconcentration of 40 mL of sample was 2.4 ng L−1 InHg. The relative standard deviation (RSD) was 2.7% (at 1 µg L−1 InHg and n=10) calculated from the peak height of absorbance signals (Gaussian-shape and reproducible peaks). This work reports the first polymer-supported IL solid phase extraction approach implemented in a flow injection on-line system for determination of Hg species in mineral, tap and river water samples.